Property alterations of Sn-0.6Cu-0.05Ni-Ge lead-free solder by Ag, Bi, In and Sb addition - KANLAYASIRI, Kannachai; KONGCHAYASUKAWAT, Rachata (My University, 2018)
The Sn-Cu-Ni-Ge solder is a strong challenger to the Sn-Ag-Cu (SAC) solders as a replacement for the Sn-Pb eutectic solder. This research investigated the effects of addition of Ag, Bi, In, and Sb on the physical properties of the Sn-0.6Cu-0.05Ni-Ge (SCNG) lead-free solder and the interfacial reaction with the Cu substrate. The melting behavior, microstructure, tensile strength, and wettability of the SCNG–x (x=Ag, Bi, In, Sb) solders were examined. The findings revealed that the introduction of Ag, Bi, In, and Sb minimally altered the solidus temperature, liquidus temperature, and tensile strength of the solder. However, the cooling behavior and solidified microstructure of the solder were affected by the concentration of the alloying elements. The wettability of the SCNG solder was improved with the doping of the alloying elements except Sb. The thickness of intermetallic layer was increased by the addition of the alloying elements and was related to the cooling behavior of the solder. The morphology of intermetallic layer between the SCNG–x solders and the Cu substrate was different from that of the typical SAC solders. In conclusion, alloying the SCNG solder with Ag, Bi, In or Sb is able to improve particular properties of the solder.
Keywords: alloying effect; lead-free solder; physical properties; Sn-Cu-Ni-Ge solder